Single‐Crystal Elastic Properties of Aluminum Oxynitride (AlON) from Brillouin Scattering. Issue 4 (19th January 2016) - Satapathy, Sikhanda; Ahart, Muhtar; Dandekar, Dattatraya; Hemley, Russell J.; Schuster, Brian; Khoma, Petro
Abstract : The Brillouin light scattering technique was used to determine experimentally the three independent elastic constants of cubic aluminum oxynitride at the ambient condition. They are C 11 = 334.8 ± 1.8 G P a, C 12 = 164.4 ± 1.2 G P a, and C 44 = 178.6 ± 1.1 G P a . Its bulk modulus is 221.2 GPa. The magnitude of Zener anisotropic ratio is 2.1 similar to other spinels. The anisotropic nature of the material is shown by a large variation in the Young's modulus and Poisson's ratio with crystallographic directions. The material was found to be auxetic in certain orientations.